Peran Supervisi Akademik dalam Meningkatkan Kualitas Implementasi Kurikulum di Lembaga Pendidikan Islam - Rizda Nirmala Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Academic supervision is a crucial aspect of Islamic education management that plays a strategic role in enhancing the quality of curriculum implementation. This study aims to analyze the role of academic supervision in strengthening curriculum execution within Islamic educational institutions. The method employed is a qualitative literature review, examining various scholarly sources related to academic supervision and curriculum implementation in the context of Islamic education. The findings indicate that academic supervision functions not only as a monitoring mechanism but also as a process for professional development of teachers and adaptation of the curriculum to Islamic values. Systematic and collaborative supervision enhances teachers’ motivation and competence while ensuring the curriculum’s relevance to students’ needs and local contexts. The implications of this study underscore the importance of reinforcing academic supervision as a fundamental pillar in adaptive and sustainable Islamic education management, capable of addressing contemporary challenges without compromising religious values.